2008
DOI: 10.1017/s1138741600004200
|View full text |Cite
|
Sign up to set email alerts
|

Both Freud and Hoffman are Right: Anxious-Aggressive and Empathic Dimensions of Guilt

Abstract: The purpose of the study was to confirm a model which proposed two basic dimensions in the subjective experience of guilt, one anxious-aggressive and the other empathic, as well as another dimension associated but not intrinsic to it, namely, the associated negative emotions dimension. Participants were 360 adolescents, young adults and adults of both sexes. They were asked to relate one of the situations that most frequently caused them to experience feelings of guilt and to specify its intensity and that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
1
4
0
13
Order By: Relevance
“…Nevertheless, the intensity of habitual guilt is probably not only related to a higher or lower level of interpersonal sensitivity. In a previous study using the same sample as in the present one (Etxebarria & Apodaca, 2008), we confirmed that subjective experiences of guilt include two basic emotional components -one empathic and the other anxious-aggressive -with the former being the predominating factor in some experiences and the latter in others. The empathic component mainly includes a feeling of sympathy for the person affected by the individual's actions or omissions, as well as a certain element of sadness; the anxious-aggressive component, on the other hand, includes anxiety, outward anger and inward anger, as well as, once again, a certain element of sadness.…”
supporting
confidence: 88%
“…Nevertheless, the intensity of habitual guilt is probably not only related to a higher or lower level of interpersonal sensitivity. In a previous study using the same sample as in the present one (Etxebarria & Apodaca, 2008), we confirmed that subjective experiences of guilt include two basic emotional components -one empathic and the other anxious-aggressive -with the former being the predominating factor in some experiences and the latter in others. The empathic component mainly includes a feeling of sympathy for the person affected by the individual's actions or omissions, as well as a certain element of sadness; the anxious-aggressive component, on the other hand, includes anxiety, outward anger and inward anger, as well as, once again, a certain element of sadness.…”
supporting
confidence: 88%
“…68 Σε αντίθεση με την προαναφερθείσα θεώρηση της ενοχής ως απόλυτα δυσπροσαρμοστικής κατάστασης, σύγχρονες προσεγγίσεις υποστηρίζουν ότι δεν σχετίζεται απαραίτητα με νευρωτικά συμπτώματα, εφόσον όμως συνδέεται με τις έννοιες της «έγνοιας» για τον πλησίον -και κατά συνέπεια με την ικανότητα ενσυναίσθησης -αλλά και τη συγχωρητικότητα. 69,70 Αντίθετα, η ενοχή μπορεί να έχει δυσπροσαρμοστικό χαρακτήρα όταν σχετίζεται με την αναμονή καταδίκης και την πεποίθηση περί μη αναστρεψιμότητας, θέματα που μπορεί να γίνουν αντικείμενο επεξεργασίας σε ένα ψυχοθεραπευτικό πλαίσιο με άξονα τη συγχωρητικότητα και μάλιστα τη συγχωρητικότητα προς τον εαυτό.…”
Section: συγχωρητικότητα και ψυχοθεραπείαunclassified
“…67 Μπορούν να αναγνωρισθούν τουλάχιστον τρεις τύποι ενοχών: ενοχή λόγω διαπροσωπικής πρό- Σε αντίθεση με την προαναφερθείσα θεώρηση της ενοχής ως απόλυτα δυσπροσαρμοστικής κατάστασης, σύγχρονες προσεγγίσεις υποστηρίζουν ότι δεν σχετίζεται απαραίτητα με νευρωτικά συμπτώματα, εφόσον όμως συνδέεται με τις έννοιες της «έγνοιας» για τον πλησίον -και κατά συνέπεια με την ικανότητα ενσυναίσθησης -αλλά και τη συγχωρητικότητα. 69,70 Αντίθετα, η ενοχή μπορεί να έχει δυσπροσαρμοστικό χαρακτήρα όταν σχετίζεται με την αναμονή καταδίκης και την πεποίθηση περί μη αναστρεψιμότητας, θέματα που μπορεί να γίνουν αντικείμενο επεξεργασίας σε ένα ψυχοθεραπευτικό πλαίσιο με άξονα τη συγχωρητικότητα και μάλιστα τη συγχωρητικότητα προς τον εαυτό.…”
Section: πτωχή εναισθησία και ψύχωσηunclassified